Positive electrode active material for non-aqueous electrolyte secondary battery, method for producing positive electrode active material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery
Patent Information
- Application Number
- JP2023125672
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-02-26
- Filing Date
- 2023-08-01
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2039-02-26
AI Technical Summary
Using lithium transition metal oxides with a high nickel content (91 mol% or more) as a positive electrode active material in non-aqueous electrolyte secondary batteries leads to deteriorated charge/discharge cycle characteristics and increased charge transfer resistance, resulting in decreased battery capacity.
Incorporating sulfate ions into lithium transition metal oxides with a nickel content of 91 mol% or more, specifically within the range of 0.02 to 0.50 mol% based on the total number of sulfate ions, and controlling the half-width of the (208) plane diffraction peak between 0.30° and 0.50°, enhances the alignment between the Li and transition metal layers, improving ionic conductivity and reducing charge transfer resistance.
This approach effectively suppresses the deterioration of charge/discharge cycle characteristics, reduces charge transfer resistance, and maintains battery capacity by ensuring smoother lithium ion movement and modified surface conductivity.
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode active material for a non-aqueous electrolyte secondary battery and the technology of non-aqueous electrolyte secondary batteries.
Background Art
[0002] In recent years, as a secondary battery with high output and high energy density, a non-aqueous electrolyte secondary battery including a positive electrode, a negative electrode, and a non-aqueous electrolyte, which performs charge and discharge by moving lithium ions or the like between the positive electrode and the negative electrode, has been widely used.
[0003] As the positive electrode active material used for the positive electrode of the non-aqueous electrolyte secondary battery, for example, the following are known.
[0004] [[ID=Z19]] For example, Patent Document 1 discloses a positive electrode active material containing a lithium transition metal oxide represented by the general formula NiM(OH)2 (where M represents at least one element selected from transition metals other than Ni, alkaline earth metal elements, Al, Ga, In, and Si) and being monodispersed primary particles.
[0005] Also, for example, Patent Document 2 discloses a positive electrode active material containing a lithium transition metal oxide represented by the general formula Li (1+δ) Mn x Ni y Co (1-x-y) O2, wherein δ, x, and y satisfy the relationships of -0.15 < δ < 0.15, 0.1 < x ≦ 0.5, and 0.5 < x + y ≦ 1.0, respectively.
Prior Art Documents
Patent Documents
[0006]
Patent Document 1
Patent Document 2
Summary of the Invention
Problems to be Solved by the Invention
[0007] By the way, when a lithium transition metal oxide in which the proportion of Ni is 91 mol% or more based on the total number of moles of metal elements excluding Li is used as a positive electrode active material, it is possible to increase the capacity of a non-aqueous electrolyte secondary battery, but there is a problem that the charge-discharge cycle characteristics deteriorate. In addition, for the purpose of improving the charge-discharge cycle characteristics, it is also conceivable to add a metal element other than Ni, but simply adding other metal elements may increase the charge transfer resistance during charge and discharge, and as a result, the battery capacity may decrease.
[0008] Therefore, the present disclosure aims to provide a positive electrode active material for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery capable of suppressing a decrease in charge-discharge cycle characteristics and suppressing an increase in charge transfer resistance and a decrease in battery capacity when using a lithium transition metal oxide in which the proportion of Ni is 91 mol% or more based on the total number of moles of metal elements excluding Li.
Means for Solving the Problem
[0009] The positive electrode active material for a non-aqueous electrolyte secondary battery according to one aspect of the present disclosure has a Ni- and Al-containing lithium transition metal oxide. The proportion of Ni in the lithium transition metal oxide is 91 mol% or more based on the total number of moles of metal elements excluding Li. The lithium transition metal oxide contains 0.02 mol% or more of sulfate ions. The lithium transition metal oxide has a half-value width n of the diffraction peak of the (208) plane of the X-ray diffraction pattern by X-ray diffraction satisfying 0.30° ≤ n ≤ 0.50°. In the lithium transition metal oxide, a SO4 compound is attached to the particle surface of the lithium transition metal oxide or is incorporated into the secondary particles of the lithium transition metal oxide. The SO4 compound is at least one of Al2(SO4)3, Ti(SO4)2, MnSO4, Nb2(SO4)3, Si(SO4)2, Mo(SO4)3, Fe2(SO4)3, BaSO4, CaSO4, CuSO4, MgSO4, SrSO4, ZnSO4.
[0010] One embodiment of the present disclosure of a non-aqueous electrolyte secondary battery is characterized by comprising a positive electrode having the above-mentioned positive electrode active material for a non-aqueous electrolyte secondary battery. [Effects of the Invention]
[0011] According to one aspect of this disclosure, it is possible to suppress the deterioration of charge-discharge cycle characteristics, as well as the increase in charge transfer resistance and the decrease in battery capacity during charging and discharging. [Modes for carrying out the invention]
[0012] A positive electrode active material for a non-aqueous electrolyte secondary battery, according to one aspect of this disclosure, comprises a Ni and Al-containing lithium transition metal oxide, wherein the proportion of Ni in the lithium transition metal oxide is 91 mol% or more relative to the total number of moles of metal elements excluding Li, the lithium transition metal oxide contains 0.02 mol% or more of sulfate ions, and the lithium transition metal oxide is characterized in that the full width at half maximum n of the diffraction peak of the (208) plane in the X-ray diffraction pattern obtained by X-ray diffraction is 0.30° ≤ n ≤ 0.50°. The reason why the decrease in charge-discharge cycle characteristics, the increase in charge transfer resistance during charge-discharge, and the decrease in battery capacity are suppressed when this positive electrode active material for a non-aqueous electrolyte secondary battery is used is not fully clear, but it is presumed to be as follows.
[0013] Ni and Al-containing lithium transition metal oxides have a layered structure, for example, consisting of a transition metal layer (such as Ni and Al), a Li layer, and an oxygen layer. The charge-discharge reaction of the battery proceeds as Li ions in the Li layer reversibly move in and out. Here, the full width at half maximum of the diffraction peak of the (208) plane in the X-ray diffraction pattern is an indicator of the fluctuation in the arrangement between the Li layer and the transition metal layer. When this value is within the predetermined range, it is thought that there is a moderate fluctuation in the arrangement between the Li layer and the transition metal layer, and the binding of Li ions in the Li layer is somewhat relaxed. Therefore, during the charge-discharge reaction, the movement of Li ions in and out of the Li layer becomes smoother, and the deterioration of the charge-discharge cycle characteristics is suppressed. Furthermore, by including the predetermined amount of sulfate ions in the lithium transition metal oxide, the surface of the lithium transition metal oxide is modified, and its ionic conductivity is uniquely increased. This is thought to suppress the increase in charge transfer resistance, and consequently, the decrease in battery capacity.
[0014] The following describes an example of a non-aqueous electrolyte secondary battery using a positive electrode active material for non-aqueous electrolyte secondary batteries, which is one aspect of this disclosure.
[0015] An example of an embodiment of a non-aqueous electrolyte secondary battery comprises a positive electrode, a negative electrode, and a non-aqueous electrolyte. A separator is preferably provided between the positive and negative electrodes. Specifically, it has a structure in which a wound-type electrode body, in which the positive and negative electrodes are wound around a separator, and the non-aqueous electrolyte are housed in an outer casing. The electrode body is not limited to a wound-type electrode body; other forms of electrode bodies may be used, such as a laminated electrode body in which the positive and negative electrodes are laminated with a separator in between. Furthermore, the form of the non-aqueous electrolyte secondary battery is not particularly limited, and examples include cylindrical, prismatic, coin-type, button-type, and laminate-type batteries.
[0016] The following describes in detail the positive electrode, negative electrode, non-aqueous electrolyte, and separator used in a non-aqueous electrolyte secondary battery, which is an example of an embodiment.
[0017] <Positive electrode> The positive electrode is composed of, for example, a positive current collector such as a metal foil and a positive electrode active material layer formed on the positive current collector. For the positive current collector, a foil of a metal stable within the potential range of the positive electrode such as aluminum, a film having such a metal disposed on its surface layer, or the like can be used. The positive electrode active material layer contains, for example, a positive electrode active material, a binder, and a conductive material.
[0018] The positive electrode is obtained by, for example, applying and drying a positive electrode composite material slurry containing a positive electrode active material, a binder, a conductive material, etc. on the positive current collector to form a positive electrode active material layer on the positive current collector, and rolling the positive electrode active material layer.
[0019] The positive electrode active material contains a lithium transition metal oxide containing Ni and Al. The ratio of Ni to the total molar number of metal elements excluding lithium in the lithium transition metal oxide is 91 mol% or more, preferably in the range of 91 mol% to 99 mol%, and more preferably in the range of 91 mol% to 96 mol%. If the ratio of Ni is less than 91 mol%, it is difficult to increase the capacity of the battery in the first place.
[0020] Al in the lithium transition metal oxide containing Ni and Al may be uniformly dispersed, for example, within the crystal structure of the Ni-containing lithium transition metal oxide, or may be present in a part of the crystal structure. Also, in the production stage of the lithium transition metal oxide, a part of the Al contained in the crystal structure may precipitate on the particle surface of the lithium transition metal oxide, but this precipitated Al is also the Al contained in the lithium transition metal oxide.
[0021] The lithium transition metal oxide containing Ni and Al may contain elements other than Al, and is represented by, for example, the following general formula. Li x Ni a Co b Al c M d O2(1)
[0022] In the above formula, a indicating the proportion of Ni may be x ≥ 0.91, preferably 0.91 ≤ x ≤ 0.99, and more preferably 0.91 ≤ x ≤ 0.96. In the above formula, b indicating the proportion of Co is preferably b < 0.06, and more preferably 0.005 ≤ b ≤ 0.045 in terms of suppressing the deterioration of charge-discharge cycle characteristics and the like. In the above formula, c indicating the proportion of Al is preferably 0.03 < c, and more preferably 0.04 ≤ c ≤ 0.06 in terms of suppressing the deterioration of charge-discharge cycle characteristics and the like.
[0023] M in the above formula is not particularly limited as long as it is an element other than Li, Ni, Al, and Co. For example, at least one element selected from Ti, Nb, Mn, Si, Mo, Zr, V, Fe, Mg, Cr, Cu, Sn, Ta, W, Na, K, Ba, Sr, Bi, Be, Zn, Ca, and B can be mentioned. Among these, in terms of suppressing the deterioration of charge-discharge cycle characteristics and the like, M in the above formula is preferably at least one element selected from Ti, Nb, Mn, Si, and Mo. In the above formula, d indicating the proportion of M is preferably 0 ≤ d ≤ 0.03, and more preferably 0.005 ≤ d ≤ 0.025.
[0024] In the above formula, x indicating the proportion of Li preferably satisfies 0.95 ≤ x ≤ 1.10, and more preferably satisfies 0.97 ≤ x ≤ 1.03 in terms of improving battery capacity and the like.
[0025] The Ni- and Al-containing lithium transition metal oxide contains sulfate ions. The sulfate ions include any form, such as when attached to the particle surface of the lithium transition metal oxide as a SO4 compound, when incorporated into the secondary particles of the lithium transition metal oxide as a SO4 compound, and when contained in the crystal structure of the Ni- and Al-containing lithium transition metal oxide.
[0026] Examples of SO4 compounds that are attached to the particle surface or incorporated into secondary particles include Al2(SO4)3, Ti(SO4)2, MnSO4, Nb2(SO4)3, Si(SO4)2, Mo(SO4)3, Fe2(SO4)3, BaSO4, CaSO4, CuSO4, MgSO4, SrSO4, and ZnSO4.
[0027] The sulfate ion content in Ni and Al-containing lithium transition metal oxides should be 0.02 mol% or more, but preferably in the range of 0.02 mol% to 0.12 mol%, and more preferably in the range of 0.03 to 0.1. Here, the sulfate ion content is measured as follows.
[0028] A sample solution obtained by adding 1 g of Ni and Al-containing lithium transition metal oxide to 50 mL of pure water is shaken at room temperature for 24 hours. After stirring, the sample solution is filtered and the filtrate is collected. The amount of sulfate ions in the collected filtrate is measured by ion chromatography. The content of the elements constituting the Ni and Al-containing lithium transition metal oxide can also be measured using inductively coupled plasma atomic emission spectrometer (ICP-AES), electron beam microanalyzer (EPMA), energy dispersive X-ray spectrometer (EDX), etc.
[0029] In Ni and Al-containing lithium transition metal oxides, the full width at half maximum (FWHM) n of the (208) plane diffraction peak in the X-ray diffraction pattern obtained by X-ray diffraction is preferably 0.30° ≤ n ≤ 0.50°, but more preferably 0.30° ≤ n ≤ 0.45°, in order to suppress the deterioration of charge-discharge cycle characteristics. If the FWHM n of the (208) plane diffraction peak is less than 0.30°, the binding of Li ions in the Li layer is stronger compared to when the above range is satisfied, and the charge-discharge cycle characteristics deteriorate. Also, if the FWHM n of the (208) plane diffraction peak exceeds 0.50°, the crystallinity of the Ni-containing Li transition metal oxide deteriorates compared to when the above range is satisfied, the framework of the crystal structure becomes brittle, and the charge-discharge cycle characteristics deteriorate.
[0030] The X-ray diffraction pattern was obtained by powder X-ray diffraction using a powder X-ray diffractometer (manufactured by Rigaku Corporation, product name "RINT-TTR", source Cu-Kα) under the following conditions. Measurement range: 15-120° Scan speed: 4° / min Analysis range: 30-120° Background; B-spline Profile function; Split type pseudo-Voigt function Constraint condition; Li(3a) + Ni(3a)=1 Ni(3a) + Ni(3b) = y ICSD No.; 98-009-4814
[0031] The content of Ni and Al-containing lithium transition metal oxide is preferably 90% by mass or more, and preferably 99% by mass or more, relative to the total mass of the positive electrode active material for non-aqueous electrolyte secondary batteries, in order to effectively suppress, for example, a decrease in charge-discharge cycle characteristics, a decrease in charge transfer resistance during charge-discharge, or a decrease in battery capacity.
[0032] Furthermore, the positive electrode active material for the non-aqueous electrolyte secondary battery of this embodiment may contain other lithium transition metal oxides in addition to the Ni and Al-containing lithium transition metal oxides. Examples of other lithium transition metal oxides include lithium transition metal oxides with a Ni content of 0 mol% to less than 91 mol%.
[0033] An example of a method for producing lithium transition metal oxides containing Ni and Al will be described.
[0034] A method for producing Ni-containing lithium transition metal oxides comprises, for example, a first step of mixing a Ni-containing compound, a Li compound, a metal element-containing SO4 compound, and a metal element-containing non-SO4 compound, and a second step of calcining the mixture.
[0035] The Ni-containing compound used in the first step may be a composite compound containing other elements such as Al or Co in addition to Ni, for example, an oxide containing Ni. The Li compound used in the first step is, for example, lithium carbonate, lithium hydroxide, etc.
[0036] The metal element-containing SO4 compounds used in the first step include SO4 compounds containing metal elements such as Al, Ti, Nb, Mn, Si, Mo, Fe, Ba, Ca, Cu, Mg, Sr, and Zn. Examples include Al2(SO4)3, Ti(SO4)2, MnSO4, Nb2(SO4)3, Si(SO4)2, Mo(SO4)3, Fe2(SO4)3, BaSO4, CaSO4, CuSO4, MgSO4, SrSO4, and ZnSO4.
[0037] The non-SO4 compound containing a metal element used in the first step is a compound containing the same or different elements as the metal element contained in the SO4 compound, and examples include hydroxides or oxides containing metal elements such as Al, Ti, Nb, Mn, Si, Mo, Fe, Ba, Ca, Cu, Mg, Sr, and Zn.
[0038] By adding both a metal element-containing SO4 compound and a metal element-containing non-SO4 compound, it becomes easy to control the full width at half maximum (FWHM) of the (208) plane diffraction peak in the final Ni and Al-containing lithium transition metal oxide to the predetermined range. While it is possible to control the amount of sulfate ions in the Ni and Al-containing lithium transition metal oxide to the predetermined range by mixing a Ni-containing compound, a Li compound, and a metal element-containing SO4 compound and calcining the mixture, in this case, it becomes difficult to control the FWHM of the (208) plane diffraction peak in the final Ni and Al-containing lithium transition metal oxide to the predetermined range.
[0039] The mixing ratio of the metal element-containing SO4 compound and the metal element-containing non-SO4 compound is preferably in the range of 1:9 to 7:3. If the proportion of the metal element-containing SO4 compound is too low, it may not be possible to control the amount of sulfate ions contained in the final Ni and Al-containing lithium transition metal oxide within the above-described range. If the proportion of the metal element-containing SO4 compound is too high, the amount of Li present in the crystal structure of the final Ni and Al-containing lithium transition metal oxide may decrease, leading to a decrease in battery capacity.
[0040] In the second step, the mixture obtained in the first step is calcined at a predetermined temperature and time to obtain the Ni and Al-containing lithium transition metal oxide according to this embodiment. The calcination of the mixture in the second step is preferably in the range of 500°C to 900°C. The calcination time is preferably 6 to 24 hours. The calcination of the mixture obtained in the second step is preferably carried out in an oxygen stream.
[0041] The following describes the other materials included in the positive electrode active material layer.
[0042] Examples of conductive materials included in the positive electrode active material layer include carbon black, acetylene black, Ketjen black, and carbon powder such as graphite. These may be used individually or in combination of two or more types.
[0043] Examples of binders included in the positive electrode active material layer include fluorine-based polymers and rubber-based polymers. Examples of fluorine-based polymers include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), or modified versions thereof, while examples of rubber-based polymers include ethylene-propylene-isoprene copolymers and ethylene-propylene-butadiene copolymers. These may be used individually or in combination of two or more.
[0044] <Negative electrode> The negative electrode comprises a negative electrode current collector, such as a metal foil, and a negative electrode active material layer formed on the negative electrode current collector. The negative electrode current collector can be a metal foil that is stable in the negative electrode potential range, such as copper, or a film with the metal arranged on its surface. The negative electrode active material layer includes, for example, a negative electrode active material, a binder, a thickener, etc.
[0045] The negative electrode can be obtained, for example, by applying and drying a negative electrode mixture slurry containing a negative electrode active material, a thickener, and a binder onto a negative electrode current collector to form a negative electrode active material layer on the negative electrode current collector, and then rolling the negative electrode active material layer.
[0046] The negative electrode active material contained in the negative electrode active material layer is not particularly limited as long as it is a material capable of intercalating and releasing lithium ions. Examples include carbon materials, metals capable of forming alloys with lithium, or alloy compounds containing such metals. As carbon materials, graphites such as natural graphite, non-graphitizable carbon, and artificial graphite, as well as cokes, can be used. As alloy compounds, those containing at least one metal capable of forming alloys with lithium can be used. Silicon and tin are preferred elements capable of forming alloys with lithium, and silicon oxide and tin oxide, which are formed by the combination of these elements with oxygen, can also be used. Furthermore, a mixture of the above carbon material and a compound of silicon or tin can be used. In addition to the above, materials such as lithium titanate, which have a charge-discharge potential higher than that of carbon materials, can also be used.
[0047] As the binder included in the negative electrode active material layer, for example, fluorine-based polymers, rubber-based polymers, etc., can be used, as in the case of the positive electrode, but styrene-butadiene copolymer (SBR) or a modified version thereof may also be used. As the binder included in the negative electrode active material layer, fluorine-based resins, PAN, polyimide-based resins, acrylic-based resins, polyolefin-based resins, etc., can be used, as in the case of the positive electrode. When preparing the negative electrode mixture slurry using an aqueous solvent, it is preferable to use styrene-butadiene rubber (SBR), CMC or its salts, polyacrylic acid (PAA) or its salts (PAA-Na, PAA-K, etc., or partially neutralized salts), polyvinyl alcohol (PVA), etc.
[0048] Examples of thickening agents included in the negative electrode active material layer include carboxymethylcellulose (CMC) and polyethylene oxide (PEO). These may be used individually or in combination of two or more.
[0049] <Non-aqueous electrolytes> A non-aqueous electrolyte comprises a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous electrolyte is not limited to a liquid electrolyte (non-aqueous electrolyte solution), but may also be a solid electrolyte using a gel-like polymer or the like. Examples of non-aqueous solvents include esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of two or more of these. The non-aqueous solvent may contain halogen-substituted solvents in which at least some of the hydrogen atoms in the solvent are replaced with halogen atoms such as fluorine.
[0050] Examples of the above esters include cyclic carbonate esters such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; linear carbonate esters such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylic acid esters such as γ-butyrolactone (GBL) and γ-valerolactone (GVL); and linear carboxylic acid esters such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), ethyl propionate, and γ-butyrolactone.
[0051] Examples of the above ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, cyclic ethers such as crown ethers, 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, and methylphenyl ether. Examples include chain ethers such as ethylphenyl ether, butylphenyl ether, pentylphenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.
[0052] As the halogen-substituted product, it is preferable to use fluorinated cyclic carbonate esters such as fluoroethylene carbonate (FEC), fluorinated linear carbonate esters, or fluorinated linear carboxylic acid esters such as methyl fluoropropionate (FMP).
[0053] The electrolyte salt is preferably a lithium salt. Examples of lithium salts include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 ) x (1 < x < 6, n is 1 or 2), LiB 10 Cl 10 , LiCl, LiBr, LiI, lithium chloroborane, lithium lower aliphatic carboxylate, borate salts such as Li2B4O7, Li(B(C2O4)F2), imide salts such as LiN(SO2CF3)2, LiN(C1F 2l+1 SO2)(C m F 2m+1 SO2){l, m are integers of 0 or more}, etc. The lithium salt may be used alone or in combination of two or more. Among these, from the viewpoints of ionic conductivity, electrochemical stability, etc., it is preferable to use LiPF6. The concentration of the lithium salt is preferably 0.8 to 1.8 mol per 1 L of the non-aqueous solvent.
[0054] <Separator> For example, a porous sheet having ion permeability and insulating properties can be used as the separator. Specific examples of porous sheets include microporous thin films, woven fabrics, and nonwoven fabrics. Suitable materials for the separator include polyethylene, olefin resins such as polypropylene, and cellulose. The separator may be a laminate having a cellulose fiber layer and a thermoplastic resin fiber layer such as an olefin resin, or a separator with an aramid resin or the like coated on its surface may be used. A filler layer containing an inorganic filler may be formed at the interface between the separator and at least one of the positive electrode and the negative electrode. Examples of inorganic fillers include oxides containing at least one of titanium (Ti), aluminum (Al), silicon (Si), and magnesium (Mg), phosphate compounds, or those whose surfaces are treated with hydroxides or the like. The filler layer can be formed, for example, by coating a slurry containing the filler onto the surface of the positive electrode, the negative electrode, or the separator. [Examples]
[0055] The present invention will be further described below with reference to examples, but the present invention is not limited to these examples.
[0056] <Example 1> [Fabrication of positive electrode active material] A composite oxide containing Ni, Co, and Al (Ni 0.92 Co 0.03 Al 0.05A mixture of O2, LiOH, and Ti(SO4)2 and Ti(OH)4 in a molar ratio of 3:7 was mixed to a molar ratio of 100:101:1. This mixture was calcined in an oxygen stream at 700°C for 20 hours to obtain a lithium transition metal oxide. The sulfate ion content of the obtained lithium transition metal oxide was measured to be 0.03 mol%. Furthermore, the proportions of Ni, Co, Al, and Ti relative to the total number of moles of Ni, Co, Al, and Ti in the obtained lithium transition metal oxide were measured to be 91 mol%, 3 mol%, 5 mol%, and 1 mol%, respectively. In addition, the full width at half maximum (FWHM) of the diffraction peak of the (208) plane in the obtained lithium transition metal oxide was 0.44°. The measurement method was as described above. This lithium transition metal oxide was used as the positive electrode active material in Example 1.
[0057] <Example 2> A lithium transition metal oxide was prepared in the same manner as in Example 1, except that a mixture of Ti(SO4)2 and Ti(OH)4 in a molar ratio of 7:3 was used. The sulfate ion content in this lithium transition metal oxide was 0.06 mol%, the Ni content was 91 mol%, the Co content was 3 mol%, the Al content was 5 mol%, and the Ti content was 1 mol%, with a full width at half maximum (FWHM) of the (208) plane diffraction peak being 0.45°. This lithium transition metal oxide was used as the positive electrode active material in Example 2.
[0058] <Example 3> A composite oxide containing Ni, Co, and Al (Ni 0.92 Co 0.03 Al 0.05 A lithium transition metal oxide was prepared in the same manner as in Example 1, except that a mixture of O2, LiOH, Al2(SO4)3, and Ti(OH)4 in a molar ratio of 3:7 was mixed to a molar ratio of 100:101:1. The sulfate ion content in the lithium transition metal oxide was 0.04 mol%, the Ni content was 91 mol%, the Co content was 3 mol%, the Al content was 5.3 mol%, and the Ti content was 0.7 mol%, and the full width at half maximum (FWHM) of the diffraction peak of the (208) plane was 0.41°. This lithium transition metal oxide was used as the positive electrode active material in Example 3.
[0059] <Example 4> A lithium transition metal oxide was prepared in the same manner as in Example 3, except that a mixture of Al2(SO4)3 and Ti(OH)4 in a molar ratio of 7:3 was used. The sulfate ion content in this lithium transition metal oxide was 0.12 mol%, the Ni content was 91 mol%, the Co content was 3 mol%, the Al content was 5.7 mol%, and the Ti content was 0.3 mol%. The full width at half maximum (FWHM) of the (208) plane diffraction peak was 0.39°. This lithium transition metal oxide was used as the positive electrode active material in Example 4.
[0060] <Example 5> A composite oxide containing Ni, Co, and Al (Ni 0.94 Co 0.015 Al 0.045 A lithium transition metal oxide was prepared in the same manner as in Example 1, except that a mixture of O2, LiOH, MnSO4, and Al(OH)3 in a molar ratio of 3:7 was mixed to a molar ratio of 100:101:1.5. The sulfate ion content in the lithium transition metal oxide was 0.03 mol%, the Ni content was 92.5 mol%, the Co content was 1.5 mol%, the Al content was 5 mol%, and the Mn content was 1 mol%. The full width at half maximum (FWHM) of the diffraction peak of the (208) plane was 0.33°. This lithium transition metal oxide was used as the positive electrode active material in Example 5.
[0061] <Example 6> A lithium transition metal oxide was prepared in the same manner as in Example 5, except that a mixture of MnSO4 and Al(OH)3 in a molar ratio of 7:3 was used. The sulfate ion content in this lithium transition metal oxide was 0.07 mol%, the Ni content was 92.5 mol%, the Co content was 1.5 mol%, the Al content was 5.5 mol%, and the Mn content was 0.5 mol%. The full width at half maximum (FWHM) of the diffraction peak of the (208) plane was 0.37°. This lithium transition metal oxide was used as the positive electrode active material in Example 6.
[0062] <Example 7> A composite oxide containing Ni, Co, and Al (Ni 0.94 Co0.015 Al 0.045 A lithium transition metal oxide was prepared in the same manner as in Example 1, except that a mixture of O2, LiOH, Al2(SO4)3, and LiNbO3 in a molar ratio of 3:7 was mixed to a molar ratio of 100:101:1.5. The sulfate ion content in the lithium transition metal oxide was 0.04 mol%, the Ni content was 92.5 mol%, the Co content was 1.5 mol%, the Al content was 5 mol%, and the Nb content was 1 mol%. The full width at half maximum (FWHM) of the diffraction peak of the (208) plane was 0.37°. This lithium transition metal oxide was used as the positive electrode active material in Example 7.
[0063] <Example 8> A lithium transition metal oxide was prepared in the same manner as in Example 7, except that a mixture of Al2(SO4)3 and LiNbO3 in a molar ratio of 7:3 was used. The sulfate ion content in this lithium transition metal oxide was 0.12 mol%, the Ni content was 92.5 mol%, the Co content was 1.5 mol%, the Al content was 5.5 mol%, and the Nb content was 0.5 mol%. The full width at half maximum (FWHM) of the diffraction peak of the (208) plane was 0.41°. This lithium transition metal oxide was used as the positive electrode active material in Example 6.
[0064] <Example 9> A composite oxide containing Ni, Co, and Al (Ni 0.945 Co 0.005 Al 0.050 A lithium transition metal oxide was prepared in the same manner as in Example 1, except that a mixture of O2, LiOH, and Al2(SO4)3 and SiO2 in a molar ratio of 7:3 was mixed to a molar ratio of 100:101:1. The sulfate ion content in the lithium transition metal oxide was 0.05 mol%, the Ni content was 93.5 mol%, the Co content was 0.5 mol%, the Al content was 5.7 mol%, and the Nb content was 0.3 mol%, and the full width at half maximum (FWHM) of the (208) plane diffraction peak was 0.34°. This lithium transition metal oxide was used as the positive electrode active material in Example 9.
[0065] <Example 10> A composite oxide containing Ni, Co, and Al (Ni0.955 Co 0.005 Al 0.04 A lithium transition metal oxide was prepared in the same manner as in Example 1, except that a mixture of O2, LiOH, Al2(SO4)3, and Ti(OH)4 in a molar ratio of 1:9 was mixed to a molar ratio of 100:101:3.5. The sulfate ion content in the lithium transition metal oxide was 0.03 mol%, the Ni content was 92 mol%, the Co content was 0.5 mol%, the Al content was 4.5 mol%, and the Ti content was 3 mol%, and the full width at half maximum (FWHM) of the diffraction peak of the (208) plane was 0.39°. This lithium transition metal oxide was used as the positive electrode active material in Example 10.
[0066] <Example 11> A composite oxide containing Ni, Co, and Al (Ni 0.94 Co 0.015 Al 0.045 A lithium transition metal oxide was prepared in the same manner as in Example 1, except that a mixture of O2, LiOH, and Ti(SO4)2 and LiNbO3 in a molar ratio of 7:3 was mixed to a molar ratio of 100:101:1.5. The sulfate ion content in the lithium transition metal oxide was 0.05 mol%, the Ni content was 93 mol%, the Co content was 1.3 mol%, the Al content was 4.2 mol%, the Ti content was 1 mol%, and the Nb content was 0.5 mol%, and the full width at half maximum (FWHM) of the diffraction peak of the (208) plane was 0.34°. This lithium transition metal oxide was used as the positive electrode active material in Example 11.
[0067] <Example 12> A composite oxide containing Ni, Co, and Al (Ni 0.94 Co 0.015 Al 0.045A lithium transition metal oxide was prepared in the same manner as in Example 1, except that a mixture of O2, LiOH, and Ti(SO4)2 and LiNbO3 in a molar ratio of 5:5 was mixed to a molar ratio of 100:101:1. The sulfate ion content in the lithium transition metal oxide was 0.04 mol%, the Ni content was 93 mol%, the Co content was 1.5 mol%, the Al content was 4.5 mol%, the Ti content was 0.5 mol%, and the Nb content was 0.5 mol%, and the full width at half maximum (FWHM) of the diffraction peak of the (208) plane was 0.37°. This lithium transition metal oxide was used as the positive electrode active material in Example 12.
[0068] <Example 13> A composite oxide containing Ni and Al (Ni 0.955 Al 0.045 A lithium transition metal oxide was prepared in the same manner as in Example 1, except that a mixture of O2, LiOH, and Al2(SO4)3 and Li2MoO4 in a molar ratio of 2:8 was mixed to a molar ratio of 100:101:0.6. The sulfate ion content in the lithium transition metal oxide was 0.03 mol%, the Ni content was 95 mol%, the Al content was 4.5 mol%, and the Mo content was 0.5 mol%, and the full width at half maximum (FWHM) of the (208) plane diffraction peak was 0.34°. This lithium transition metal oxide was used as the positive electrode active material in Example 13.
[0069] <Example 14> A composite oxide containing Ni, Co, and Al (Ni 0.94 Co 0.015 Al 0.045 A lithium transition metal oxide was prepared in the same manner as in Example 1, except that a mixture of O2, LiOH, and Ti(SO4)2 and Li2MoO4 in a molar ratio of 5:5 was mixed to a molar ratio of 100:101:1. The sulfate ion content in the lithium transition metal oxide was 0.04 mol%, the Ni content was 93 mol%, the Co content was 1.5 mol%, the Al content was 4.5 mol%, the Ti content was 0.5 mol%, and the Mo content was 0.5 mol%, and the full width at half maximum (FWHM) of the diffraction peak of the (208) plane was 0.35°. This lithium transition metal oxide was used as the positive electrode active material in Example 14.
[0070] <Comparative Example 1> A composite oxide containing Ni, Co, and Al (Ni 0.92 Co 0.04 Al 0.04 A lithium transition metal oxide was prepared in the same manner as in Example 1, except that O2, LiOH, and Ti(SO4)2 were mixed in a molar ratio of 100:101:1. The sulfate ion content in the lithium transition metal oxide was 0.1 mol%, the proportion of Ni was 91 mol%, the proportion of Co was 4 mol%, the proportion of Al was 4 mol%, and the proportion of Ti was 1 mol%, and the full width at half maximum (FWHM) of the diffraction peak of the (208) plane was 0.25°. This lithium transition metal oxide was used as the positive electrode active material for Comparative Example 1.
[0071] <Comparative Example 2> A composite oxide containing Ni, Co, and Al (Ni 0.92 Co 0.03 Al 0.05 A lithium transition metal oxide was prepared in the same manner as in Example 1, except that O2, LiOH, and Al2(SO4)3 were mixed in a molar ratio of 100:101:1. The sulfate ion content in this lithium transition metal oxide was 0.17 mol%, the Ni content was 91 mol%, the Co content was 3 mol%, and the Al content was 6 mol%. The full width at half maximum (FWHM) of the diffraction peak of the (208) plane was 0.27°. This lithium transition metal oxide was used as the positive electrode active material for Comparative Example 2.
[0072] <Comparative Example 3> A composite oxide containing Ni, Co, and Al (Ni 0.935 Co 0.015 Al 0.05 A lithium transition metal oxide was prepared in the same manner as in Example 1, except that O2, LiOH, and MnSO4 were mixed in a mass ratio of 100:101:1.5. The sulfate ion content in the lithium transition metal oxide was 0.13 mol%, the Ni content was 92 mol%, the Co content was 1.5 mol%, the Al content was 5 mol%, and the Mn content was 1.5 mol%. The full width at half maximum (FWHM) of the diffraction peak of the (208) plane was 0.28°. This lithium transition metal oxide was used as the positive electrode active material for Comparative Example 3.
[0073] <Comparative Example 4> A composite oxide containing Ni, Co, and Al (Ni 0.93 Co 0.03 Al 0.04 A lithium transition metal oxide was prepared in the same manner as in Example 1, except that O2 and LiOH were mixed in a molar ratio of 100:101. The sulfate ion content in the lithium transition metal oxide was 0.01 mol%, the Ni content was 93 mol%, the Co content was 3 mol%, and the Al content was 4 mol%, and the full width at half maximum (FWHM) of the (208) plane diffraction peak was 0.23°. This lithium transition metal oxide was used as the positive electrode active material for Comparative Example 4.
[0074] <Comparative Example 5> A composite oxide containing Ni, Co, and Al (Ni 0.935 Co 0.01 Al 0.055 A lithium transition metal oxide was prepared in the same manner as in Example 1, except that O2, LiOH, and Al were mixed in a molar ratio of 100:101:1. The sulfate ion content in this lithium transition metal oxide was 0.01 mol%, the Ni content was 92.5 mol%, the Co content was 1 mol%, and the Al content was 6.5 mol%, with a full width at half maximum (FWHM) of the (208) plane diffraction peak being 0.28°. This lithium transition metal oxide was used as the positive electrode active material for Comparative Example 5.
[0075] [Fabrication of the positive electrode] 91 parts by mass of the positive electrode active material from Example 1, 7 parts by mass of acetylene black as a conductive material, and 2 parts by mass of polyvinylidene fluoride as a binder were mixed. The mixture was kneaded using a kneader (TK Hibiscus Mix, manufactured by Primix Corporation) to prepare a positive electrode mixture slurry. Next, the positive electrode mixture slurry was applied to a 15 μm thick aluminum foil, and the coating was dried to form a positive electrode active material layer on the aluminum foil. This was used as the positive electrode for Example 1. Positive electrodes for the other examples and comparative examples were prepared in the same manner.
[0076] [Preparation of non-aqueous electrolytes] Ethylene carbonate (EC), methyl ethyl carbonate (MEC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 3:3:4. Lithium hexafluoride phosphate (LiPF6) was dissolved in this mixed solvent to a concentration of 1.2 mol / liter to prepare a non-aqueous electrolyte.
[0077] [Preparation of test cells] An electrode body was fabricated by stacking the positive electrode of Example 1 and a negative electrode made of lithium metal foil facing each other with a separator in between. Next, the electrode body and the non-aqueous electrolyte were inserted into an aluminum casing to fabricate a test cell. Test cells for the other examples and comparative examples were fabricated in the same manner.
[0078] [Measurement of capacity retention rate in charge-discharge cycle characteristics] Under an ambient temperature of 25°C, the test cells of each example and comparative example were charged with a constant current of 0.2C until the battery voltage reached 4.3V, then charged with a constant voltage of 4.3V until the current value reached 0.05mA, and finally discharged with a constant current of 0.2C until the battery voltage reached 2.5V. This charge-discharge cycle was performed 20 times, and the capacity retention rate of the test cells in each example and comparative example during the charge-discharge cycle was determined using the following formula. A higher value indicates that the degradation of the charge-discharge cycle characteristics is suppressed. Capacity retention rate = (Discharge capacity at 20th cycle / Discharge capacity at 1st cycle) × 100
[0079] [Measurement of charge transfer resistance] After charging the test cells of each example and comparative example under the above charging conditions, AC impedance measurements were performed in the range of 10 mHz to 100 kHz, and Cole-Cole plots were created. The charge transfer resistance was determined from the size of the approximately semicircles appearing in the obtained Cole-Cole plots.
[0080] Table 1 shows the battery capacity (discharge capacity in the first cycle), charge transfer resistance, and capacity retention rate of the test cells for each example and comparative example.
[0081] [Table 1]
[0082] Examples 1 to 14 all exhibited high capacity retention and battery capacity, as well as low charge transfer resistance. On the other hand, Comparative Examples 1 to 5 exhibited either low capacity retention, low battery capacity, or high charge transfer resistance. From these results, it can be concluded that by using a positive electrode active material having a Ni and Al-containing lithium transition metal oxide, wherein the proportion of Ni in the lithium transition metal oxide is 91 mol% or more relative to the total number of moles of metal elements excluding Li, the lithium transition metal oxide contains 0.02 mol% or more of sulfate ions, and the full width at half maximum n of the diffraction peak of the (208) plane in the X-ray diffraction pattern obtained by X-ray diffraction is 0.30° ≤ n ≤ 0.50°, it is possible to suppress the deterioration of charge-discharge cycle characteristics, suppress the increase in charge transfer resistance during charge-discharge, and consequently suppress the deterioration of battery capacity.
Claims
1. a Ni- and Al-containing lithium transition metal oxide; The proportion of Ni in the lithium transition metal oxide is 91 mol % or more based on the total number of moles of metal elements excluding Li, the lithium transition metal oxide contains 0.02 mol % or more of sulfate ions, The lithium transition metal oxide has an X-ray diffraction pattern in which the half width n of the diffraction peak of the (208) plane is in the range of 0.30°≦n≦0.50°, The lithium transition metal oxide has SO 4 The compound is attached to the secondary particles of the lithium transition metal oxide, or SO 4 The compound is incorporated The SO 4 The compound is Al 2 (SO 4 ) 3 , Ti(SO 4 ) 2 , MnSO 4 , Nb 2 (SO 4 ) 3 , Si(SO 4 ) 2 , Mo(SO 4 ) 3 , Fe 2 (SO 4 ) 3 , BaSO 4 , CaSO 4 , CuSO 4 , MgSO 4 , SrSO 4 , ZnSO 4 The positive electrode active material for a non-aqueous electrolyte secondary battery is at least one of the above.
2. The SO 4 The compound is Al 2 (SO 4 ) 3 , Ti(SO 4 ) 2 , MnSO 4 , Nb 2 (SO 4 ) 3 , Si(SO 4 ) 2 , Mo(SO 4 ) 3 The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 , wherein the positive electrode active material is at least one of the following:
3. A non-aqueous electrolyte secondary battery comprising a positive electrode containing the positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2.